External validity of a population-based study on osteoporosis and fracture: Comparison of mortality and fracture rate in participants and non-participants. (August 2014) - Wihlborg, Axel; Åkesson, Kristina; Gerdhem, Paul
Abstract : Background and purpose — Little is known about the characteristics of non-participants in epidemiological studies. We evaluated external validity by comparing fracture and mortality rate in participants and non-participants in a longitudinal study on risk factors for fracture. Methods — 1, 604 randomly selected women, 75 years of age, were invited to attend a study on osteoporosis and fracture. 1, 044 women attended the study (participants) and 560 women did not participate (non-participants). Fracture data for all were obtained prospectively from radiographic records. Mortality data were obtained through the population register. Mean follow-up was 13 (11–15) years. Cumulative survival was compared with the log-rank test. Fracture incidence rates per 1, 000 person-years were compared with Mann-Whitney U-tests. In addition, fracture comparisons were made with the cumulative incidence function and Gray's test. Results — 454 participants (44%) died during the follow-up, as compared to 372 of the non-participants (66%) (p < 0.001). The fracture incidence rate for any type of fracture was 43 for participants and 47 for non-participants (p = 1.0). The fracture incidence rate for typical osteoporotic fracture was 36 for participants and 39 for non-participants (p = 0.6). The corresponding values for distal forearm fracture were 11 and 7 (p = 0.002), they were 8 and 9 for proximal humerus fracture (p = 0.9), 13 and 10 for vertebral fracture (p = 0.007), 15 and 18 for hip fracture (p = 0.8), and they were 6 and 5 for pelvic fracture (p = 0.3). The cumulative incidence function confirmed the results. Interpretation — Our findings suggest that participants had a lower mortality rate than non-participants. Distal forearm and vertebral fractures were more frequent in participants. However, the external validity for fractures in general appeared to be satisfactory.